Pengaruh Model Pembelajaran Team Quiz terhadap Hasil Belajar Siswa Kelas VII MTs Negeri 1 Lombok Barat Pada Mata Pelajaran Sejarah Kebudayaan Islam - Agusnul Hakim; Muhammad Fahrurrozi (Action Research Journal, 2024)
This research aims to determine whether or not there is an influence of the team quiz learning model on the learning outcomes of class VII students at MTs Negeri 1 Lombok Barat in the Islamic Cultural History subject in the Khulafaur Rasyidin material for the 2023–2024 academic year. This research applies a quasi-experimental approach by providing treatment to a sample group with the aim of measuring cause and effect and concluding the effect of the treatment. The design used in the research used a one-group pretest-posttest design. The sample selection technique was carried out using purposive sampling, and the final data analysis technique used the paired t-test. The research findings show that there is an influence of the team quiz learning model on the learning outcomes of class VII students at MTs Negeri 1 Lombok Barat in the Islamic Cultural History subject for the 2023–2024 academic year. As can be seen from the results of the analysis and data processing carried out by researchers in this study, In the research, it was found that the total significance value was 0.00 < 0.05, so it could be concluded that H0 was rejected and H1 was accepted, meaning that the team quiz learning model could have an influence on learning outcomes.